2017 IEEE 24th Symposium on Computer Arithmetic (ARITH) 2017
DOI: 10.1109/arith.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Neumann Series or Exact Matrix Inversion for Massive MIMO?

Abstract: Approximate matrix inversion based on Neumann series has seen a recent increased interest motivated by massive MIMO systems. There, the matrices are in many cases diagonally dominant, and, hence, a reasonable approximation can be obtained within a few iterations of a Neumann series. In this work, we clarify that the complexity of exact methods are about the same as when three terms are used for the Neumann series, so in this case, the complexity is not lower as often claimed. The second common argument for Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The centralized matrix inversion can be performed either using an exact [23] or an approximate [12], [24], [25] algorithm. As shown in [26], the complexity is similar for the best exact algorithm and a Neumann series approximation with three terms. In both cases a 20 × 20 matrix inversion can be performed in less than 40 µs using one processing element running at 200 MHz.…”
Section: Example: Lte-like System Specificationsmentioning
confidence: 83%
“…The centralized matrix inversion can be performed either using an exact [23] or an approximate [12], [24], [25] algorithm. As shown in [26], the complexity is similar for the best exact algorithm and a Neumann series approximation with three terms. In both cases a 20 × 20 matrix inversion can be performed in less than 40 µs using one processing element running at 200 MHz.…”
Section: Example: Lte-like System Specificationsmentioning
confidence: 83%
“…The convergence rates of approximate-inversion based data detectors will significantly deteriorate in such scenarios. A study in [16] suggested that exact matrix inversion based detectors are viable alternatives from both complexity and latency perspective. A few implementations of exact-inversion based data detection have been proposed in [17] and [18].…”
Section: A Relevant Prior Artmentioning
confidence: 99%
“…Several linear and non-linear detectors have been proposed. The linear detectors such as Maximum Likelihood (ML), Zero Forcing (ZF), and Minimum Mean Square Error (MMSE) have been considered for massive MIMO signal detection [8][9][10]. ML detection provides optimal performance, but it is computationally infeasible for a system such as massive MIMO involving thousands of antennas.…”
Section: Relevant Prior Art and Motivationmentioning
confidence: 99%